"DISTANCED" TIMES: INVESTIGATING PRE-SERVICE MUSIC TEACHERS' EXPERIENCES ON ONLINE TEACHING AND LEARNING DURING THE COVID-19 PANDEMIC - Miruna Luana MIULESCU; Florentina - Lavinia MATEI (National Centre for Policy and Evaluation in Education, 2021)
The technology use is flourishing in a growing set of educational contexts. Music education is no exception, seeing more and more learning practices be actively incorporated into educational frameworks. Our study seeks to investigate the online teaching and learning experiences of music university students who are participating in the pre-service teacher education during the Covid-19 pandemic. The participants of the present study are pre-service music students (n=22) enrolled in the teaching education programme in their 2nd or 3rd year at the university. By making use of a phenomenological qualitative inquiry, data was collected through participating at semi-structured interviews via ZOOM videotelephony software in January and February 2021. The key findings indicate a neither overtly positive or negative teaching and learning experience, even if the students had to navigate an avalanche of offline learning technology requirements both as students and teachers in a limited amount of time. The results of the study indicate that teacher training programmes should consider the move to virtual teaching and learning as an opportunity for change and to go beyond the emergency online practices and develop quality online educational activities.